You smell and taste and fell and see and hear - Murphy, Mary (DK Inc, 1997)
In this picture book some puppies explore their senses of smell, taste, feeling, seeing and hearing. Their mother is a warm and reassuring presence who sometimes shares their experiences and is sometimes there just to run home to